Paradigma Hakikat Manusia: Antara Liberalisme, Sosialisme, Dan Islam Dalam Membangun Pendidikan Agama Islam Yang Transformatif - Mukhtar, Dertha; Aprison, Wedra (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This article examines the paradigm of human nature from three major perspectives: liberalism, socialism, and Islam, and explores how the synthesis of these values can contribute to the development of a transformative Islamic Religious Education (PAI). This study employs a qualitative method based on a literature review with a comparative analysis of accredited journal articles. The findings reveal that liberalism emphasizes individual freedom, socialism stresses collective solidarity, and Islam integrates both within a transcendental spiritual dimension. Transformative PAI emerges from this balance, fostering education that cultivates faith, knowledge, and social responsibility. These findings highlight the significance of an integrative paradigm as the foundation for developing Islamic educational theory and practice in the contemporary era.